Environmental presence and toxicological outcomes of the herbicide pendimethalin in teleost fish - Ivantsova, Emma (Ecotoxicology (London, England), 2024)
© 2024. The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.